Quantification of total sBCMA in human plasma by peptide-level immunocapture LC-MS/MS - Johanna Paris; Alexandra Tavernier; Sylvie Bethegnies; Sandrine Descloux; Olivier Fedeli (Journal of Mass Spectrometry and Advances in the Clinical Lab)
Background: B-cell maturation antigen (BCMA) is a membrane protein that is overexpressed in multiple myeloma cells and can be targeted with biotherapeutic agents. BCMA is naturally shed by γ-secretase, leading to the formation of soluble BCMA (sBCMA), which circulates in the blood. sBCMA can affect the efficacy of BCMA-targeted therapies and act as a drug sink. Additionally, sBCMA can interfere with pharmacokinetic measurements when BCMA is directly targeted. Therefore, quantification of this biomarker during clinical trials is essential to assess the effective dose and understand pharmacokinetic results. When quantifying sBCMA using ligand binding assays or hybrid assays, the biotherapeutic can interfere with the capture of sBCMA, leading to an underestimation of its levels. Methods: Samples were denatured, reduced, and alkylated prior to trypsin digestion. sBCMA peptide enrichment was performed using anti-peptide polyclonal antibodies. Reversed-phase chromatographic separation was conducted on a biocompatible C18 column with an analysis time of sixteen minutes per sample. The SCIEX QTRAP 5500 mass spectrometer operated in multiple reaction monitoring mode. The calibration curve was prepared by spiking recombinant sBCMA into monkey plasma. Results: The parallelism between the authentic and surrogate matrices, as well as between the endogenous and recombinant proteins, was validated. Comparisons were made between protein and peptide level hybrid assays, with the peptide level approach effectively removing the interference of the biotherapeutic. Additionally, the peptide level immunocapture LC-MS/MS demonstrated ligand tolerance. Conclusion: The peptide level immunocapture LC-MS/MS analysis eliminated the interference of anti-BCMA biotherapeutics, allowing for the quantification of total sBCMA in clinical samples while achieving a LLOQ of 10 ng/mL.